Conservation status of threatened vertebrates in Netherlands (Zoological Records and Reviews, 2024)
The Netherlands, despite being one of Europe's most densely populated and agriculturally intensified countries, harbours a vertebrate fauna whose threatened proportion has increased substantially over the past three decades. This study provides a comprehensive, multi-taxon assessment of the conservation status of threatened vertebrates in theNetherlands, integrating the 2023 Dutch Red List evaluations with population trend data, habitat condition indices, andpolicy compliance metrics for five vertebrate groups: freshwater fish (n = 38 assessed species), amphibians (n = 18),reptiles (n = 12), breeding birds (n = 184), and terrestrial mammals (n = 68). Of 320 assessed species, 118 (36.9%)qualify as Threatened (Critically Endangered, Endangered, or Vulnerable) under Dutch Red List criteria. Freshwater fishshow the highest threatened proportion (60.5% of assessed species), driven by hydrological modification andeutrophication of the Rhine-Meuse delta system. Breeding birds show the greatest absolute decline in the threatenedproportion since 1990 (+14.2 percentage points), with farmland birds (Alauda arvensis, Limosa limosa, Vanellusvanellus) constituting the most rapidly declining guild. Habitat condition indices based on Natura 2000 qualityassessments were significantly lower for threatened than for non-threatened species across all five groups(Mann-Whitney p < 0.001 in all cases). Species distribution modelling under IPCC RCP 4.5 and 8.5 scenarios projectsfurther contraction of suitable habitat for 74% of currently threatened species by 2050. These findings identify prioritytaxa and landscape sectors for targeted intervention under the EU Nature Restoration Law (2024/1991) and DutchNational Programme Rural Area.